Fragility of short‐chain poly(lactic acid)s derivatives by combining dielectric spectroscopy and fast scanning calorimetry. Issue 14 (20th May 2021) - Moghaddam, Sareh Mahmoudian; Quelennec, Blandine; Delpouve, Nicolas; Atawa, Bienvenu; Delbreilh, Laurent; Saiter–Fourcin, Allisson; Passaglia, Elisa; Fiori, Stefano
Abstract: Low‐molecular‐mass bio‐polyesters, such as lactic acid oligomers, constitute a growing category of plasticizers for poly (lactic acid), since they show good compatibility and are respectful of the environment. This study focuses on the glass transition of a series of oligomers with different molecular weights, with the aim of investigating how their associated dynamics occur. Dielectric and calorimetric results are combined to study the molecular mobility in a large temperature range. In comparison with poly (lactic acid), the oligomers exhibit a lower fragility index and smaller cooperative rearranging regions. Among oligomers, the fragility is clearly dependent on the molecular weight, whereas the variations of the cooperativity are subtler. Abstract :